A Process Addictions Course for Counselor Training Programs - Amanda L Giordano; Audrey Malacara; Sarah Agarwal (Teaching and Supervision in Counseling, 2019)
We proposed the implementation of a course dedicated to the etiology and treatment of process addictions in counselor-training programs. We described the nature of the course and results of paired samples t-tests examining differences in 23 students’ preferences, competence, importance, and understanding at the beginning and end of the semester. Specifically, student preference for working with process addictions, competence, and understanding of process addictions significantly increased with large effect sizes at the completion of the course. We concluded with a description of implications for counselor educators and counselor-training programs.
Keywords: Counselor training programs; behavioral addictions; counselor preparation